IMPACT OF ETHNIC IDENTITY ON SOCIAL DISTANCE OF PERSONALITY - I B Kudinova; A I Kislitsin; A B Nurekeeva (Peoples' Friendship University of Russia (RUDN University), 2015)
In the present paper, we discuss the results of an empirical research. The study involved students of the Russian Peoples' Friendship University. The sample consisted of the representatives of the Latin Americans, Chinese and Russians. The main techniques used in the study are "Types of Ethnic Identity" by G.U. Soldatova and S.V. Ryzhova and "Social Distance Scale" by E. Bogardus. The main objective of the empirical study was to identify the level of ethnic identity formation in the representatives of the Russian nationality and the representatives of other countries, and then analyze how a particular level of ethnic identity, formed in Russians and other nationalities influences the social distance between each other in a multicultural interpersonal space. In order to establish the relationships between the ethnic identity and social distance in different samples the correlation analysis was used. The results of it gave the opportunity to determine the dependence of ethnic identity and social distance at a statistically significant level and to identify some specific features of this interdependence, due to both gender and national and ethnic origins. Furthermore, the identified patterns of the interdependence of the studied phenomena are determined by the success of self-realization of the actors. The higher the level of self-realization, the closer the social distance and the higher the level of tolerance of the individual is